2020
DOI: 10.1186/s12885-020-07205-5
|View full text |Cite
|
Sign up to set email alerts
|

Is thyroid excision mandatory with laryngectomy in carcinoma larynx?

Abstract: Background: Advanced stage operable cancers of larynx are treated with total laryngectomy including thyroid resection in most of the cases, which may expose patient to hypothyroidism and hypoparathyroidism. The requirement of thyroidectomy during Total Laryngectomy is controversial. Methods: A cross sectional observational study was set out to review preoperative clinical and radiological assessment; intraoperative and histopathological findings; and follow-up data to predict thyroid gland invasion in the sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…28 Baghel et al recommended thyroidectomy only in gross radiological or intraoperative thyroid gland involvement and subglottic extension. 25 In another study, 88% of the patients who had lobectomies during laryngectomy needed thyroid supplementation later in life. 29…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…28 Baghel et al recommended thyroidectomy only in gross radiological or intraoperative thyroid gland involvement and subglottic extension. 25 In another study, 88% of the patients who had lobectomies during laryngectomy needed thyroid supplementation later in life. 29…”
Section: Discussionmentioning
confidence: 98%
“…Isolated total laryngectomy causes hypothyroidism in 20 to 63% of the patients. 25 The morbidity is worse in patients undergoing adjuvant radiation to the neck. 14 Preoperative radiation with salvage laryngectomy results in a greater risk of hypothyroidism than laryngectomy, followed by postoperative radiation.…”
Section: Discussionmentioning
confidence: 99%
“…For decades Total laryngectomy with ipsilateral hemi thyroidectomy has been the treatment of choice by head and neck surgeons worldwide. Both total thyroidectomy and hemi thyroidectomy may render the patient at risk of permanent or temporary hypothyroidism and/or hypoparathyroidism 19 leaving patients on the mercy of permanent replacement with Thyroxin and Calcium supplements respectively adding to their morbidity and increasing cost, no of hospital visits and financial burden both over the patient and the hospital. However no risk of hypothyroidism or hypoparathyroidism is associated with Thyroid sparing Total Laryngectomy 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Baghel et al studied the need for thyroid excision along with laryngectomy in carcinoma larynx, and concluded that the invasion of thyroid gland by laryngeal cancer is uncommon, and hence advocated total thyroidectomy to be done along with total laryngectomy in cases which had gross clinical, radiological or intraoperative thyroid gland involvement, subglottic extension and thyroid cartilage invasion. 19 Ceylan et al 20 in their study also concluded that there may not be a need to perform thyroidectomy in all total laryngectomy cases and recommended thyroidectomy to be done in laryngeal carcinoma cases with subglottic extension and advanced hypopharyngeal tumours. There is, however, no doubt that lesions involving the glottic larynx with significant subglottic extension mandate an ipsilateral thyroid lobectomy be done, to facilitate ipsilateral tracheo-oesophageal lymph node clearance.…”
Section: Study Year Number Of Casesmentioning
confidence: 97%